Importance of the Use of Teaching Resources in Teaching and Learning Biological Science for Visual Stimulation of Students - Suárez-Ramos, Josmary Celinda (2017)
This article aims to conduct a literature review on documentary sources approaching aspects related to the importance of the use of didactic resources in the teaching and learning process of biological sciences. The paper focuses on the visual stimulation of students, and considers important information in the field of biological sciences, pedagogy and didactics. Through a systematic review, bibliographical and electronic sources were selected; they were published in a period from 1983 to 2013. The article describes some of the main didactic resources producing greater visual impact in the students and turning into meaningful learning through their incorporation into the cerebral cortex. Findings suggest that the individuals’ learning is mediated by the nervous system and the sensory organs. Likewise, studies have verified that the sense of sight is the system of primary representation for most human beings, and the teaching strategies combining vision with hearing have considerable possibilities of being more effective. It is concluded that the use of adequate didactic resources is indispensable to optimize students’ learning in terms of content in the area of biological sciences. So it is recommended that teachers consider these realities when planning strategies to teach their classes.